Gabon : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report, 2020)
In response to a request from the Gabonese authorities, a mission from the Fiscal Affairs Department of the IMF visited Libreville to conduct an evaluation of public investment management, using the Public Investment Management Assessment methodology. The report highlights that enhancing the efficiency of public investment is essential, given Gabon's current budget constraints. Improving public investment management (PIM) should help stem the declines in public investment efficiency in Gabon. In terms of infrastructure quality, public investment efficiency has fallen to half of the expected optimal level, compared to a 20 percent decline both worldwide and in Sub-Saharan Africa, as well as a 31 percent decline in member states of the Central African Economic and Monetary Union. The findings of the PIM assessment reveal structural deficiencies in planning procedures and institutional arrangements. Eight recommendations are put forward to enhance PIM efficiency in the short and medium terms, with three urgent steps needed to rationalize planning.